Cochrane Database of Systematic Reviews 2007
DOI: 10.1002/14651858.cd004716.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Supportive therapy for schizophrenia

Abstract: There are insufficient data to identify a difference in outcome between supportive therapy and standard care. There are several outcomes, including hospitalisation and general mental state, indicating advantages for other psychological therapies over supportive therapy but these findings are based on a few small studies. Future research would benefit from larger trials that use supportive therapy as the main treatment arm rather than the comparator.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 161 publications
0
2
0
Order By: Relevance
“…Other alterations may better serve clients with schizophrenia. A recent Cochrane review suggested that a cognitivebehavioral approach, compared with a supportive therapy approach, is efficacious for these clients, though the authors cautioned that more research is needed (Buckley, Pettit, & Adams, 2007). Quitline counseling usually relies heavily on behavioral change strategies that include cognitive techniques.…”
Section: Problem-solving Focusmentioning
confidence: 99%
“…Other alterations may better serve clients with schizophrenia. A recent Cochrane review suggested that a cognitivebehavioral approach, compared with a supportive therapy approach, is efficacious for these clients, though the authors cautioned that more research is needed (Buckley, Pettit, & Adams, 2007). Quitline counseling usually relies heavily on behavioral change strategies that include cognitive techniques.…”
Section: Problem-solving Focusmentioning
confidence: 99%
“…2. ) To measure the effects of supportive therapy for patients with schizophrenia Not enough data collected to make any reasonable assumptions (Buckley et al 2007) CMHT, community mental health teams. that the review process was flawed if there were insufficient RCT to draw valid conclusions and that the inclusion of non-randomized studies is warranted in these cases.…”
Section: Limitations Of the Studymentioning
confidence: 99%